2010
DOI: 10.1007/s13187-010-0142-6
|View full text |Cite
|
Sign up to set email alerts
|

Learning Through Service: Student Perceptions on Volunteering at Interprofessional Hepatitis B Student-run Clinics

Abstract: Student-run clinics (SRCs) are widespread, but studies on their educational impact are limited. We surveyed preclinical medical, nursing, and pharmacy students about their experiences in a hepatitis B elective which provided opportunities to they could volunteer at hepatitis B screening and vaccination SRCs. Student responses revealed positive perceptions of the volunteer experience. Benefits included interacting with patients, developing clinical skills, providing service to disadvantaged populations, and col… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
53
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 56 publications
(59 citation statements)
references
References 19 publications
4
53
0
Order By: Relevance
“…By being exposed to under-served patient populations, the PT students improved their awareness of the social determinants of health and how they affect patient care. This finding is similar to that of Sheu and colleagues, 15,16 who found that volunteering at an SRC helped medical and nursing students understand health disparities.…”
Section: Marginalized Patient Populationssupporting
confidence: 88%
See 2 more Smart Citations
“…By being exposed to under-served patient populations, the PT students improved their awareness of the social determinants of health and how they affect patient care. This finding is similar to that of Sheu and colleagues, 15,16 who found that volunteering at an SRC helped medical and nursing students understand health disparities.…”
Section: Marginalized Patient Populationssupporting
confidence: 88%
“…17,18 These studies have also shown that volunteering at an SRC improves students' attitudes toward IPC 4,10,15 and working with marginalized patients; 18 it also improves students' understanding of health disparities 15,16 and other HCP roles. 6,15,16,19 Furthermore, volunteering at an SRC is associated with self-reported improvement in inter-professional behaviour 20 and clinical reasoning skills. 10 One study investigated the PT student experience in a US pro bono clinic, a clinical setting similar to an SRC.…”
Section: Ré Sumémentioning
confidence: 99%
See 1 more Smart Citation
“…Since research and lectures in the latter half of the 1990s began focusing on the topic of volunteering, volunteer programs have been introduced into the education system, and their effectiveness in training those who will be the future support of a democratic society in the future has been recognized. There have been reports of practical examples of volunteer activities being used in medical, pharmaceutical, and nursing education as well [2][3][4][5]. In recent years, "service learning, " with clearly defined educational goals and methods, has been introduced in educational programs; information and knowledge that can be used in their practical application have been indicated [7,8].…”
Section: Introductionmentioning
confidence: 99%
“…Some good examples include student-run clinics from the University of California, San Francisco, where interprofessional student teams care for hepatitis B patients. 15 The University of Florida provides an Interdisciplinary Family Health course that emphasizes community-based learning experiences. Underserved settings may provide a good environment for interprofessional education, with the HRSA collaborative serving as one model.…”
mentioning
confidence: 99%